IMPLICATIONS OF REFUSAL SCHOOL ON THE PSYCHIC AND ACADEMIC FACTORS OF MADRASAH IBTIDAIYAH STUDENTS - Amrih Widodo; Fauzi Annur (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2021)
Abstract:This study aims to answer two crucial problems in education, especially school refusal for Madrasah Ibtidaiyah students. First, to express the students' reasons why they do school refusal. The second is to reveal the implications for the students' psychological and academic factors. In this study, the researcher used a descriptive qualitative approach to describe natural phenomena or human manipulation phenomena. The data was obtained through an interview with the seven students of Madrasah Ibtidaiyah Negeri 1 Semarang. To analyze the data, the researcher used non-statistical methods with interactive methods developed by Miles and Huberman. This research indicated that the students refuse to go to school because of physical conditions such as getting a fever or sick and psychological conditions such as not doing the homework and being bullied. The absence of the students during the learning process, especially Mathematics, affects their academic achievement.Abstrak:Penelitian ini bertujuan untuk menjawab dua masalah krusial dalam dunia pendidikan, khususnya school refusal pada siswa Madrasah Ibtidaiyah. Pertama, untuk mengungkapkan alasan siswa melakukan penolakan sekolah. Kedua, untuk mengungkap implikasi faktor psikologis dan akademis siswa. Dalam penelitian ini peneliti menggunakan pendekatan kualitatif deskriptif untuk mendeskripsikan fenomena yang ada, baik fenomena alam maupun manipulasi manusia. Data diperoleh melalui wawancara kepada tujuh siswa Madrasah Ibtidaiyah Negeri 1 Semarang. Untuk menganalisis data, peneliti menggunakan metode non statistik dengan metode interaktif yang dikembangkan oleh Miles dan Huberman. Hasil penelitian menunjukkan bahwa siswa menolak bersekolah karena kondisi fisik seperti demam atau sakit dan kondisi psikologis seperti tidak mengerjakan PR dan di-bully. Ketidakhadiran siswa selama proses pembelajaran khususnya pelajaran Matematika mempengaruhi prestasi akademiknya.